Circulating immune complexes in acute leukemia - Cermák, J; Feyereislová, A; Horejsí, J (Neoplasma, 1989)
Circulating immune complexes (CIC) were measured at the time of diagnosis in 81 patients with acute leukemia or blast crisis of chronic myeloid leukemia using precipitation by 3.75% polyethyleneglycol. Elevated CIC levels did not adversely influence complete remission duration and survival, patients with normal CIC levels exhibited mostly shorter remission and survival than those with elevated or borderline levels. No significant correlation was observed between CIC levels and Hb, WBC, CBC, platelet count, age, serum bilirubin, total protein, fibrinogen, AST and ALT levels, presence of hepatosplenomegaly and/or lymphadenopathy, HbSAg positivity, complete remission duration and survival. The lack of correlation may be caused by altered immune response in leukemic patients, but the obtained results may also be affected by the nonspecific nature of the method used for the detection. Simultaneous detection of CIC levels by multiple tests and evaluation not only of the number but also of the composition and size of CIC may decrease the incidence of false results. Nevertheless, only the establishment of antigen-specific assays may resolve the controversies in the detection of CIC and thus contribute to a more precise assessment of the role of CIC in prognosis of cancer, as well as to the verification of reliability of using CIC as a tumor marker.
Keywords: dospělí; akutní lymfatická leukemie; Adult; Antigen-Antibody Complex; počet leukocytů; lidé; chronická myeloidní leukemie; prognóza; imunokomplex; Leukocyte Count; Remission Induction; Blast Crisis; leukemie; indukce remise; akutní myeloidní leukemie; Prognosis; Leukemia; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Leukemia, Myeloid, Acute; blastická krize; Humans